2017
DOI: 10.1111/jvs.12580
|View full text |Cite
|
Sign up to set email alerts
|

Variation of the biotic neighbourhood and topographic effects on tree survival in an old‐growth temperate forest

Abstract: Aims Tree mortality can determine forest dynamics and succession, alter nutrient cycling and contribute to tree species co‐existence. Understanding the mechanisms that maintain species diversity is a central goal of community ecology. In this study, we incorporated survival data from a 10‐yr interval census to determine whether there is significant interspecies variation in the effects of biotic neighbourhood variables and whether there is significant spatial variation in the effects of topographic variables o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 74 publications
1
4
0
Order By: Relevance
“…In our study, seedling height was positively associated with individual survival in plot C, which was consistent with previous findings [6,28,29]. Larger individuals are less sensitive to biological stress, as their greater height can allow them to gain more light resources and protect against damage by pathogens and herbivorous insects [12,53]. However, seedling height had insignificant positive effects in plots A and B. Oshima et al [54] reported different responses to seedling height among species of Dipterocarpus and Shorea.…”
Section: The Relative Importance Of Density Dependence Functional Tra...supporting
confidence: 91%
“…In our study, seedling height was positively associated with individual survival in plot C, which was consistent with previous findings [6,28,29]. Larger individuals are less sensitive to biological stress, as their greater height can allow them to gain more light resources and protect against damage by pathogens and herbivorous insects [12,53]. However, seedling height had insignificant positive effects in plots A and B. Oshima et al [54] reported different responses to seedling height among species of Dipterocarpus and Shorea.…”
Section: The Relative Importance Of Density Dependence Functional Tra...supporting
confidence: 91%
“…Thus, it is likely that the link between heterospecific neighborhood density and tree growth might not be sensitive to the variation in neighborhood radius in the Luquillo forest. Furthermore, we were not able to capture the effects of conspecific density on tree survival and growth at 5m, as previously reported (Zhu et al 2017), and the strength of the effect did not change for larger neighborhood radii. This could be because the 5m radius neighborhood was so narrow that the probability of encountering a conspecific neighbor was very small, especially for neighbor trees > 10 cm DBH.…”
Section: Accepted Articlementioning
confidence: 69%
“…The climate is temperate continental monsoon with most rainfall in summer. The mean annual temperature is −0.3°C, and the mean annual precipitation is 676 mm (Piao et al., 2013; Zhu et al., 2017). The mixed broad‐leaved Korean pine ( Pinus koraiensis ) forest is the most common vegetation type in Northeast China, and the Liangshui Reserve has a large area of these primary and undisturbed forests.…”
Section: Methodsmentioning
confidence: 99%